ANALYSIS OF THE PROVISION FOR IMPLEMENTATION OF REVERSE LOGISTICS IN THE SUPERMARKET RETAIL - Braga Junior, Sergio Silva [UNESP]; Silveira Dias Junqueira, Karina Tonelli; Silva, Dirceu da; Oliveira, Sandra Cristina [UNESP] (Univ Nove Julho, 2020)
Purpose: The objective of this research was to analyze the willingness to implement reverse logistics in supermarket retail. Methodology: Data were collected on the practice of reverse logistics from 18 supermarkets and using logistic regression to generate a model for evaluating the disposition for such practice. Originality/Relevance: In the literature, there are no studies that suggest a model for implementation and guidance for reverse logistics, since the model proposed in the present study can be applied in other areas of knowledge. Main results: As a result, it was observed that through the variables that define the characteristics of retail, it is not possible to say whether or not a supermarket will implement the reverse logistics process. Theoretical/methodological contributions: The method used can be used to build management and decision models for both industry and retail. Social/management contributions: Based on this research, companies can apply the model for decision making on the feasibility or not of implementing Reverse Logistics.
Keywords: Reverse logistics; Retail; Logistic regression